HUBUNGAN ANTARA PENGGUNAAN GADGET DENGAN SEMANGAT BELAJAR - Indah Febriyani, Nur; Hasbullah Prayitno, Nur; Umniatuzzahro (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This research aims to explore the relationship between gadget use and students' enthusiasm for learning. This research uses quantitative methods with a correlational approach. The research sample consisted of 100 junior high school students in Semarang Regency. Data was collected through a questionnaire designed to measure the frequency and type of gadget use as well as the level of student enthusiasm for learning. The data analysis technique used is simple linear regression analysis. The research results show that there is a significant negative relationship between gadget use and students' enthusiasm for learning. These findings indicate that the higher the intensity of gadget use, the lower the level of student enthusiasm for learning. In addition, in-depth analysis reveals that the use of gadgets for non-academic purposes has a greater impact on reducing enthusiasm for learning than the use of gadgets for academic purposes. Based on the results of this research, it is recommended that parents and educators supervise and limit students' use of gadgets to increase their enthusiasm for learning.